Funk brasileiro: música, comunicação e cultura - Pedro, Thomaz Marcondes Garcia (2015)
This research focus the phenomenon of Brazilian funk in the Brazilian popular music as a complex sociocultural practice, and recognizing it as a mixture of various musical and non musical elements. It is an investigation that, beside reconstructing one perspective of the development of this music, tried to establish intersections between funk and many others elements that are part of it's context and ambient. To be able to accomplish that, the theoretical ground is based on researchers from the Communication field (Martín-Barbero, Pinheiro, Souza Santos) and from the Popular Music field (Wisnik, Vargas, Rivera) that try to comprehend the cultural practices of Latin America as a complex process, hybrids and mestizos in constant movement, transformation, translation and adaptation between themselves, always avoiding comprehensions marked by dichotomy, which are typical on those fields of study. Are also a part of the theoretical basis of this work researchers that developed studies specifically about Brazilian funk (Lopes, Palombini, Facina, Sá), beside the field researches, that have resulted in reports about those experiences. The results of the research allow a deeper comprehension of funk in the Communication and popular music fields and confirm our spectating that funk is a complex phenomenon that can only be understood in the context and ambient that it has been developed. Beside some musical aspects we fuscous on the relation of funk with market, violence and sexuality. Our approach allowed "listen" to Brazilian funk in a unheard way, free from prejudice and dualist points of view, that have market a way of looking at it, typical of the conservative sectors of society that were able to criminalize this cultural practice